Simple models to estimate soybean and corn percent ground cover with vegetation indices from MODIS - Bocco, Mónica (2013)
Fil: Bocco, Mónica. Universidad Nacional de Córdoba. Facultad de Ciencias Agropecuarias; Argentina.